Micro-morphological traits of Aglaonema griffithii and its chemical and antioxidant properties - Thao Nguyen Luu; Tran Anh Tu Le; Le Pham Tan Quoc; Thu Trang Le-thi; Quoc Hung Nguyen; Hong Thien Van (Journal of Applied Botany and Food Quality)
Aglaonema griffithii Schott is a helophytic plant widely found in the southern Vietnam and some regions of southeastern Asia. The aim of this study is to provide the anatomical characteristics, chemical compounds and antioxidant activity of this species for the first time. The micro-morphological traits of the studied species are performed using the iodine green-carmine double staining method. The anatomical characteristics of the different parts of A. griffithii are used as a monograph in the herbal medicine standardization of this plant. The gas chromatography/mass spectrometry assay is also used to determine the chemical compounds in the ethanolic extracts obtained from A. griffithii. Of these, sucrose is the most abundant component found in the rhizome and petiole extracts while the leaf extract is found to be rich in phytol as the highest percent component. The antioxidant properties of the ethanol extracts of the A. griffithii leaf, rhizome, and petiole were also investigated using DPPH radical scavenging assay with IC50 values of 193.08, 234.61, and 270.65 μg/mL, respectively.